2023
DOI: 10.3390/ijms242317081
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Voluntary Morphine Intake Is Associated with Changes in Brain Structures Involved in Drug Dependence in a Rat Model of Polydrug Use

María Elena Quintanilla,
Paola Morales,
Daniela Santapau
et al.

Abstract: Chronic opioid intake leads to several brain changes involved in the development of dependence, whereby an early hedonistic effect (liking) extends to the need to self-administer the drug (wanting), the latter being mostly a prefrontal–striatal function. The development of animal models for voluntary oral opioid intake represents an important tool for identifying the cellular and molecular alterations induced by chronic opioid use. Studies mainly in humans have shown that polydrug use and drug dependence are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Conversely, studies using selectively bred rats for their high ethanol consumption have shown increased MCP1 levels in the hippocampus [37]. The reason for these disparities remains unclear, though the selection that induced high ethanol consumption in selectively bred rats may have generated a particular sensitivity to develop alterations that promote the motivation for drug consumption, which may include neuroinflammation, as it has been recently discussed [58].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, studies using selectively bred rats for their high ethanol consumption have shown increased MCP1 levels in the hippocampus [37]. The reason for these disparities remains unclear, though the selection that induced high ethanol consumption in selectively bred rats may have generated a particular sensitivity to develop alterations that promote the motivation for drug consumption, which may include neuroinflammation, as it has been recently discussed [58].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we demonstrated that chronic oxycodone administration in young female rats is associated with several neurodegenerative patterns in the brain: increased oxidative stress, astrocyte activation, decrease and disorganization in white matter, loss of myelin basic protein (MBP), and accumulation of amyloid precursor protein beta [ 25 , 26 ]. Similarly, a recent study showed that female rats with high alcohol preference became dependent on morphine, which was associated with increased oxidative stress, axonal demyelination in the prefrontal cortex, and glial striatal neuroinflammation [ 27 ].…”
Section: Introductionmentioning
confidence: 99%